The Arthropoda Diversity Booklet as a Learning Resource for Biodiversity Materials (Journal of Biology Education, 2022)
The development of science and technology has a great influence in the world of education. Educators are required to be able to increase innovation in the learning process, one of which is the use and selection of effective and efficient media. Based on an interview with a Biology teacher at Pangudi Luhur Santo Yosef High School Surakarta, learning during the pandemic has not been able to run optimally due to various obstacles such as the mindset of students towards material concepts and independence for learning. This study aims to analyze the validity, response, and readability of the Arthropod Diversity booklet product of the Bengawan Solo River in the Sukoharjo Regency. The collection of arthropod specimens from the Bengawan Solo River was carried out in Sukoharjo Regency using purposive sampling technique. The booklet is made based on the results of species collection using the Research and Development (RnD) method. Data collection techniques were carried out using interviews, questionnaires, and tests in the form of a gap test. The data analysis technique used is descriptive statistics with quantitative and qualitative data. The results showed that the arthropod diversity booklet on biodiversity material was very feasible to use with a percentage of 93.75% in the validity test by media experts and 83.33% by material experts. The Bengawan Solo River arthropod diversity booklet was also considered very well to use with a percentage of 88.12% in the response test by teachers and 88.389% by students. In addition, based on the readability test conducted by the students, it showed that 75% of the students had very good understanding of the contents of the booklet and 85.71% of the students were independent readers who could understand the contents of the booklet without any educational interaction. Based on the results above, it can be concluded that the Bengawan Solo River arthropod diversity booklet is valid and can be used in learning on biodiversity material as a companion book or learning supplement.